Efficiency of Managing the Resource Potential of University Library - Davydova, I. O. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Objective. The paper investigates the resource potential of higher education institution libraries as a tool for effective management of their activity. Methods. The author pays attention to the difference between the concepts of "resource pool" and "resource potential", which is in involving the latter in the process of library information production and service. Results. The composition of the university library's resource potential is determined. It is stated that the effective management of the resource potential requires the managers to fully evaluate the factors of the internal and external environment of the library functioning. Characterization of individual components of the university library resource potential is given, and the need for their integrated use is emphasized. Much attention is paid to library staff as a leading resource of the management system, the formation of their cognitive potential. Conclusions. It is stated that the efficiency of the activity of the modern library of the higher education institution is largely determined by the available resource potential aimed at the achievement of scientifically and educationally significant goals and objectives of strategic character. The main results of the research can be used in the process of managing the activities of the university library.